2019
DOI: 10.1590/s1517-707620190004.0831
|View full text |Cite
|
Sign up to set email alerts
|

Síntese e caracterização de nanopartículas de Fe3O4@SiO2

Abstract: RESUMO Neste trabalho foi estudada a síntese e caracterização das nanopartículas magnéticas de magnetita (Fe3O4) através da co-precipitação e, sua posterior funcionalização pela sílica (SiO2), realizada via metodologia sol-gel. A caracterização das nanopartículas foi feita por difratometria de raios X (DRX), microscopia eletrônica de transmissão (MET), espectroscopia de infravermelho com transformada de Fourier (FTIR) e medidas da variação de potencial zeta em função do pH. Os resultados obtidos mostraram que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…After digestion of the AuNP@SiO 2 samples (Figure 1a), it was not possible to detect the gold content using strategy S2 (HNO 3 + HCl + MW), and no visual changes were observed in the aspect of the remaining material (Figure 1b). This result indicates the presence of gold nanoparticles inside the nanomaterial (metal on core) is consistent with a core-shell structure, 21,22 i.e., the gold nanoparticle is covered by a nonporous silica layer, protecting the AuNP core 23 during the S2 treatment. In fact, for S2, on comparing the images of the AuNP@SiO 2 samples before and after digestion (Figures 1a and 1b, respectively), it can be observed that the proposed digestion conditions failed to extract the gold nanoparticles present in the silica.…”
Section: Resultssupporting
confidence: 63%
“…After digestion of the AuNP@SiO 2 samples (Figure 1a), it was not possible to detect the gold content using strategy S2 (HNO 3 + HCl + MW), and no visual changes were observed in the aspect of the remaining material (Figure 1b). This result indicates the presence of gold nanoparticles inside the nanomaterial (metal on core) is consistent with a core-shell structure, 21,22 i.e., the gold nanoparticle is covered by a nonporous silica layer, protecting the AuNP core 23 during the S2 treatment. In fact, for S2, on comparing the images of the AuNP@SiO 2 samples before and after digestion (Figures 1a and 1b, respectively), it can be observed that the proposed digestion conditions failed to extract the gold nanoparticles present in the silica.…”
Section: Resultssupporting
confidence: 63%